Malcolm McDonald on Marketing Planning / Understanding Marketing Plans and Strategy - Mcdonald Malcolm H. B (Kogan Page, 2008)
This book will help you to appreciate the benefits of rigorous marketing planning and will guide you through the production of a marketing plan made to work in the real world. Preface, Introduction, Understanding Marketing Planning, How Marketing Planning Fits with Corporate Planning, The Strategic Marketing Planning Process and the Marketing Plan, Defining Markets and Segments Prior to Planning, Understanding Product and Services Prior to Planning, Setting Marketing Objectives and Strategies, Advertising and Sales Promotion Strategies, Sales Strategies, Price Strategies, Place (Distribution and Customer Service) Strategies, Information and Organization, Making Marketing Planning Work, Next Steps, Index.